Analisis Yuridis Pertimbangan Hakim Mahkamah Agung Terhadap Pencabutan Pengaduan Yang Melewati Batas Waktu Dengan Menerapkan Pendekatan Restorative Justice (Analisis Yurisprudensi Mahkamah Agung No. 1600 K/Pid/2009 dan Putusan No. 2238 K/Pid.Sus/2013) - Hidayat Bastanta Sitepu; Syafruddin Kalo; Edi Yunara; Marlina Marlina (Iuris Studia: Jurnal Kajian Hukum, 2021)
The purpose of law in general to bring about or create harmony in society is clearly a noble goal as the implementation of the correctional system which is imbued with the spirit of protection which became the forerunner to the formation of a distinctive Indonesian strafrechtstheorien. We want a criminal theory that is built in addition to paying attention to developments in the international/global order, the growth of legislation (top down) but also maintaining legal values that live and are maintained in people's lives. Withdrawal of a complaint is a process in which one of the litigants wants to settle/resolve the problem in good faith because he feels that the case has been resolved by means of a family mechanism. This often happens, especially in cases of a complaint offense, the regulation on the revocation of complaints has been regulated in the provisions of Article 75 of the Criminal Code regarding the period of revocation of complaints within 3 months. In practice, there are several cases that have expired/expired in withdrawing a complaint, it is allowed to be revoked by the panel of judges. It is interesting why, because on the one hand, de jure revocation of complaints over time cannot be withdrawn and must be carried out by law, on the other hand the judge as a mouthpiece of justice overrides this provision with the consideration that "the balance is disturbed if peace and harmony are hindered by regulations". The approach method in this research is the statutory approach, the case approach, and the conceptual approach. By researching primary, secondary, and tertiary legal materials. the technique used is by means of library research. The results of the study explain that the regulation regarding the revocation of complaints that have expired has no provisions that regulate it, only limited to the revocation of complaints with a period of 3 months, namely in Article 75 of the Criminal Code. And the current legal developments, especially the judiciary, there are things that are becoming increasingly legal breakthroughs through the jurisprudence of the Supreme Court no. 1600 K/Pid/2009 which decides may withdraw the complaint even though the time has passed/expired. Of course, this must be considered in order to form rules that specifically regulate the expiration of a complaint revocation process